2016
DOI: 10.1016/j.watres.2016.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Use of dual carbon–chlorine isotope analysis to assess the degradation pathways of 1,1,1-trichloroethane in groundwater

Abstract: 16Compound-specific isotope analysis (CSIA) is a powerful tool to track contaminant fate in 17 groundwater. However, the application of CSIA to chlorinated ethanes has received little 18 attention so far. These compounds are toxic and prevalent groundwater contaminants of 19 environmental concern. The high susceptibility of chlorinated ethanes like 20 1,1,1-trichloroethane (1,1,1-TCA) to be transformed via different competing pathways (biotic 21 and abiotic) complicates the assessment of their fate in the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 54 publications
(10 reference statements)
0
26
0
Order By: Relevance
“…Local changes in groundwater mineralization have been observed compared to the background composition of groundwater in the aquifer. During the investigations of Palau et al [21], an increase of Ca 2+ , HCO 3 − , Cl − and SO 4 2− was observed within the plume of dissolved CAHs. Sulphate concentrations even exceed the EU drinking water standard (250 mg/L) [22] in some places, reaching concentration levels as high as 5 times the background concentration.…”
Section: Introductionmentioning
confidence: 93%
“…Local changes in groundwater mineralization have been observed compared to the background composition of groundwater in the aquifer. During the investigations of Palau et al [21], an increase of Ca 2+ , HCO 3 − , Cl − and SO 4 2− was observed within the plume of dissolved CAHs. Sulphate concentrations even exceed the EU drinking water standard (250 mg/L) [22] in some places, reaching concentration levels as high as 5 times the background concentration.…”
Section: Introductionmentioning
confidence: 93%
“… 13 C vs  37 Cl) 26 . The resultant slope =  13 C/ 37 Cl ≈   C/  Cl relates the isotope effects of the two elements to each other and provides a more sensitive parameter to differentiate reaction mechanisms than isotope effects from one element alone [27][28][29][30][31] . An additional advantage of dual element isotope slopes is that they are remarkably insensitive towards masking of intrinsic isotope effects that occurs when the bond breaking reaction is not rate limiting in biocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In groundwater, 1,1,1-TCA is prone to abiotic transformation to 1,1-dichloroethene (1,1-DCE) via 49 elimination, or to 1,1-dichloroethane (1,1-DCA) via reduction catalyzed either by naturally occurring 50 metals or added metals in engineered systems (Scheutz et al, 2011;Palau et al, 2016). In particular, the 51 addition of zero valent iron (ZVI) has been tested at lab and pilot scales and implemented at various sites 52 to reduce chlorinated compounds including 1,1,1-TCA (Fennell and Roberts, 1998; Agrawal et al, 2002; DCA was often found as the major daughter product and ethane as a minor by-product.…”
Section: Introduction 36mentioning
confidence: 99%